Parameter estimation of hybrid magnetic bearings system for axial flow blood pump applications with possible self-sensing capability - Cheng, Shan Bao (2009)
The active magnetic bearing (AMB) system has been widely employed in industrial applications, among which one of the most important applications is the magnetically levitated rotary blood pumps. It is because AMB can replacetraditional ball bearings and realize the non-contact support of rotating impellers/rotors of the pumps. Current state-of-the art ventricular assist devices (VADs) are magnetically suspended rotary pumps, and it is due to the advantages of the magnetic bearings: no mechanical contact between the bearing and rotor, no lubrication needed, less heat generation and lower hemolytic risk.